Living Narratively: From Theory to Experience (and Back Again) - Baldwin, Clive (Narrative Works, 2013)
On November 3, 2011, Clive Baldwin presented the fourth annual John McKendy Memorial Lecture on Narrative at St. Thomas University. The annual lecture, sponsored by the Centre for Interdisciplinary Research on Narrative (CIRN), is named for John McKendy, PhD, a member of the Sociology Department at St. Thomas University and one of the founding members of CIRN, who died tragically in 2008. What follows is a transcript of Dr. Baldwin’s lecture, with an accompanying film. A list of further reading follows the transcript.